Concurrent Chemoradiotherapy With Nedaplatin Versus Cisplatin in Patients With Stage IIB-IVA Cervical Cancer: A Randomized Phase III Trial - He, Shasha; Wang, Yan; Lai, Yulin; Cao, Xinping; Ren, Yufeng; Chen, Yong (Frontiers in Oncology, 2022)
Background: In this trial, we aimed to assess the efficacy, safety of radiotherapy with nedaplatin or cisplatin, in patients with locally advanced cervical cancer. Methods: We did an open-label, non-inferiority, phase 3, randomised, controlled trial. Eligible patients with stage IIB-IVA cervical carcinoma were randomly assigned to receive either nedaplatin or cisplatin for two cycles concurrently with radiotherapy. We reported the therapy associated harms and survival. The study was registered with chictr.org.cn, number ChiCTR1800020527. Results: We randomly assigned 68 patients to nedaplatin-based or cisplatin-based concurrent chemoradiotherapy. Study treatment was stopped early after a data analysis found a higher number of patients suffered severe hematologic harms in the nedaplatin group than in the cisplatin group. Patients in the nedaplatin group had a significantly higher frequency of grade 3-4 neutropenia than did patients in the cisplatin group (19·4% vs. 13%; P < 0·001). So as severe thrombocytopenia 16·1% vs. 4·3%, and grade 1-2 anemia 51·6% vs. 43·5%. The 1-year PFS and OS in the nedaplatin and cisplatin groups were similar. Conclusion: Our findings showed that nedaplatin-based concurrent chemoradiotherapy expressed remarkably higher severe hematologic harms which were mortal. Though the results were negative, the experiences and lessons we learned from it was important.